Implementasi Metode Rapid Application Development pada Pengembangan Aplikasi Inventory Barang - Siti Anisah (Universitas Indraprasta PGRI Jakarta, 2022)
The Faculty of Medicine and Health, Universitas Muhammadiyah Jakarta, still manually manages inventory, especially the consumables, using paper media such as in processing incoming and outgoing goods and in reporting the goods that are recorded and stored on spreadsheet tools. making it difficult to manage data. The purpose of this study is to design and build an inventory information system to facilitate the effective inventory data management process. The system development method uses Rapid Application Development (RAD). Tools in system design use UML, while system programming uses PHP and mysql database and system testing uses blackbox method. The results of this study produce an inventory of goods information system by providing convenience in managing inventory data, making the finding of goods inventory easier or faster because the system can show the goods data section, making the inventory can be accurately and easily controlled.